2014
DOI: 10.1039/c4ra02785j
|View full text |Cite
|
Sign up to set email alerts
|

Construction of multifunctional organic–inorganic hybrid Bi2S3–PLGA capsules for highly efficient ultrasound-guided radiosensitization of brachytherapy

Abstract: A novel multifunctional Bi2S3–PLGA capsule has been designed and synthesized for significantly enhancing the therapeutic efficiency of cancer brachytherapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…Other investigators also reported that biocompatible Bi 2 Se 3 NPs exhibited diminished toxicity and the potential to function as theranostic agents for radiation therapy, including multimodal imaging, radiosensitization, and PTT 149 , 150 . Moreover, several studies have revealed that Bi 2 S 3 and Bi 2 O 3 NPs could serve as radiosensitizers and enhancers for radiotherapy 151 - 156 . Alqathami et al validated and quantified the radiation dose enhancement of Bi 2 S 3 and Bi 2 O 3 NPs using phantom cuvettes and novel 3D phantoms and found that the radiation enhancement was greater when irradiating with kV X-rays compared to MV X-rays 157 .…”
Section: Metal-based Nanoenhancers For Ionizing Ramentioning
confidence: 99%
“…Other investigators also reported that biocompatible Bi 2 Se 3 NPs exhibited diminished toxicity and the potential to function as theranostic agents for radiation therapy, including multimodal imaging, radiosensitization, and PTT 149 , 150 . Moreover, several studies have revealed that Bi 2 S 3 and Bi 2 O 3 NPs could serve as radiosensitizers and enhancers for radiotherapy 151 - 156 . Alqathami et al validated and quantified the radiation dose enhancement of Bi 2 S 3 and Bi 2 O 3 NPs using phantom cuvettes and novel 3D phantoms and found that the radiation enhancement was greater when irradiating with kV X-rays compared to MV X-rays 157 .…”
Section: Metal-based Nanoenhancers For Ionizing Ramentioning
confidence: 99%
“…The proof-of-concept was demonstrated by Hainfeld et al [ 7 ] who evidence that injections of 1.9 nm gold nanoparticles (GNPs) increased the survival of tumor-bearing mice in combination with 250 kVp X-rays compared to X-rays alone. Since this pioneering work, the development of new high-Z radiosensitizers (including silver [ 8 , 9 ], gadolinium [ 10 , 11 , 12 ], hafnium [ 13 , 14 ], platinum [ 15 , 16 ], gold [ 6 , 17 , 18 ] or bismuth [ 19 , 20 ] nanoparticles) has accelerated and many studies have shown their ability, when injected into the tumor, to amplify the X-ray radiation treatment efficacy. While evidencing this potential use as a radiosensitizer, the large variations in all these experimental settings revealed the high variability of GNP effects according to different physico-chemical parameters including GNP size, shape and coating agent.…”
Section: Introductionmentioning
confidence: 99%
“…have prepared FL and CT dual‐mode imaging NPs through coating fluorescent QDs and Bi 2 S 3 NPs with silica shell. Moreover, when Bi 2 S 3 NPs are embedded in US contrast agents, such as poly(lactic‐co‐glycolic acid) (PLGA) or PFC, they can be used for both US and CT imaging. MR and CT dual‐mode imaging agents can also be obtained through hybrid MR agents with Bi‐based NPs.…”
Section: Bi‐based Nms Used For Cancer Diagnosismentioning
confidence: 99%
“…have proposed that Bi 2 Se 3 nanoplates can induce significant DNA damage in tumor cells under the radiation, and can also be cleared after 90 days of treatment with the low toxicity even at the high dose of 20 mg kg −1 mouse . At the same time, other Bi‐based NMs, such as Bi 2 O 3 NPs and Bi 2 S 3 NPs have also exhibited excellent in vitro and in vivo radiation sensitization effects.…”
Section: Bi‐based Nms Used For Cancer Therapymentioning
confidence: 99%
See 1 more Smart Citation